Kicking in soccer - Sterzing, T. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Kicking as the defining action of soccer has gained huge interest within the scientific community with respect to practice, coaching, science and technology. This paper focuses on current knowledge of soccer kicking, including its biomechanical description, skill execution, kicking techniques, performance criteria, and measurement technology. Additionally, it refers to a fairly new research aspect, the influence of soccer footwear on the kicking movement and consequently on kicking success as it has been shown that soccer footwear alters the biomechanics of kicking. Finally, future directions of research are suggested that are helpful to enhance the fundamental understanding of kicking.